Benefits, environmental risks and habitats of edible insects in Benin, West Africa - Toffa, J.; Dassou, A.; Badoussi, E.; Saliou, M.; Anagonou, C.; Loko, Y.L.E.; Tamò, Manuele (2025)
In the Republic of Benin, entomophagy is practiced in some regions and contributes to the food security and poverty reduction. However, insect farming is poorly developed and wild capture remains the main source of edible insects. This capture practice can pose health and environmental risks and raises questions about the sustainable use of edible insects as a food source. Therefore, the objective of this study was to document farmers' perceptions and knowledge of the benefits and environmental risks associated with wild-caught edible insects in order to formulate recommendations for their conservation and sustainable use. Surveys were conducted with 225 farmers from 33 villages and belonging to 6 socio-linguistic groups were performed using rural appraisal tools. The surveyed participants listed 21 main species of edible insects with a diversity of species observed in the agro-ecological zones studied. The surveyed farmers also identified environmental risks, including, soil degradation, pollution by synthetic chemical pesticides, flooding and destruction of natural habitats, while endangered species and bioaccumulation of chemicals were the most important constraints of edible insects in the study zone. In terms of benefits, most farmers highlighted those edible insects reduce pollutant gas emissions by releasing less carbon dioxide than other livestock. Edible insects also support biodegradation activities, and the recycling of organic waste into biofertilizers. Farmers also mentioned that they conserve wild edible insect populations while preserving their regenerative capacity to avoid species overexploitation. Factors influencing the socio-environmental aspects of edible insect use need to be taken into account in strategies to encourage farmers to promote sustainable edible insect collection practices. These results contribute to decision-making on the environmental safety in terms of entomophagy in Benin.